Dauru Kitābi Al-Fahmu fī Taṭwīri at Tafkīri an-Naḥwiyyi Ladā Ṭullābi al Lughah al ‘Arabiyyah fī Ma‘hadi Al Kautsar - Anto Yusran (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2025)
This study investigates the role of the Al-Fahmu book in developing grammatical thinking (tafkir nahwi) among Arabic language students at Ma’had Al-Kautsar. Arabic grammar (nahwu) plays a vital role in understanding the Qur’an and mastering the Arabic language; however, many students still perceive it as a difficult subject that depends heavily on memorization. The Al-Fahmu book addresses these challenges by presenting grammatical concepts in clear and logical Indonesian explanations, enabling students to understand the rules through reasoning rather than rote learning. Using a qualitative descriptive approach, this study analyzes the structure, presentation, and educational values of Al-Fahmu as a learning resource for Arabic grammar. The results show that the book effectively enhances students’ grammatical understanding, stimulates logical reasoning, and fosters a more reflective attitude toward language learning. It is recommended that Arabic teachers integrate Al-Fahmu into grammar instruction as a supplementary material to promote conceptual comprehension and analytical thinking.